EFFECT OF DIFFERENT TYPES OF FEED (Squid, Sea Worms, Trash Fish) ON THE LEVELS OF GONAD MATERNITY AND THE FUNDAMENTAL OF GALAH SHRIMP (Macrobrachium rosenbergii) - Alfi Zahrotun Nisa; David Hermawan; Ganjar Adhywirawan (Universitas Muhammadiyah Malang, 2023)
The availability of high-quality broodstock is a key factor in the success of giant freshwater prawn (Macrobrachium rosenbergii) hatchery operations. Broodstock nutrition, particularly the type of natural feed provided, plays an important role in supporting gonadal development and reproductive performance. Therefore, this study aimed to evaluate the effects of different natural feed types on gonad maturation and fecundity of giant freshwater prawn broodstock. The study was conducted using an experimental method with a Completely Randomized Design (CRD) consisting of four treatments: squid (Loligo sp.), sea worms, trash fish, and commercial pellets (control). Female broodstock were reared under controlled conditions, and observations were made on gonad maturity level and fecundity. Gonad maturation was assessed based on the percentage of broodstock reaching Gonad Maturity Stage III (GMS III), while fecundity was determined using the gravimetric method. Water quality parameters, including temperature, dissolved oxygen (DO), and pH, were monitored throughout the experiment. The results showed that different feed types significantly affected gonad maturation and fecundity of giant freshwater prawn broodstock. Squid feed produced the highest percentage of broodstock reaching GMS III (83%), followed by sea worms (67%), trash fish (41%), and pellets (25%). Similarly, the highest fecundity was observed in the squid treatment, reaching 28,846 ± 4,925 eggs per female, compared to 21,120 ± 2,579 eggs in the sea worm treatment, 19,644 ± 6,396 eggs in the trash fish treatment, and 16,768 ± 4,183 eggs in the control treatment. Water quality remained within optimal ranges for broodstock culture. In conclusion, squid is the most effective natural feed for enhancing gonad maturation and fecundity of giant freshwater prawn broodstock, making it a promising dietary component for improving hatchery productivity.